Not all brains are created equal: the relevance of individual differences in responsiveness to transcranial electrical stimulation - Krause, Beatrix; Cohen Kadosh, Roi (Frontiers in Systems Neuroscience, 2014)
A current issue in the research of augmentation of brain functions using transcranial electrical stimulation (tES) is the diversity and inconsistency in outcome results. Similar studies often report different results, depending on the parameters and tasks used. Such inconsistencies have led to significant doubts about the efficacy of the method in the broader scientific community, despite its promising potential for patient recovery and treatment. Evidence on the large variability in individual cortical excitability and response to tES suggests that stimulation may affect individuals differently, depending on the subject’s age, gender, brain state, hormonal levels, and pre-existing regional excitability. Certain factors might even lead to the reversal of polarity-dependent effects, and therefore have crucial implications for neurorehabilitation and cognitive enhancement. Research paradigms may have to be refined in the future to avoid the confounding effects of such factors.